Fatigue growth behavior for surface crack in welding joints under combined compressive and bending stresses. (August 2015) - Shen, Wei; Yan, Renjun; Liu, Enqian; Xu, Lin
Highlights: Carry out biaxial compressive–bending fatigue testing. Analyze the influence of compressive stress on the fatigue life. An equivalent stress intensity factor and crack growth model are proposed. Abstract: It has been demonstrated by experiments that crack can grow under cyclic compressive loading. However, it is difficult to observe and describe accurately by mathematical methods. In addition, cracks may close under compressive loading, which also increases the complexity of the problem. The fatigue growth behavior for surface cracks under biaxial loadings was studied by fatigue tests of HTS-A steel. According to experimental evidences, it is concluded that the transverse compressive stress not only changes the fracture morphology but also affect crack propagation life. Considering the influence of the compressive stress, this paper proposed an equivalent SIF and crack growth model subjected to compressive and bending stresses on the basis of McEvily formula. Finally, comparisons are made between prediction results and experimental data.